Literature Review Ketepatan Pengodean ICD-10 External Cause di Rumah Sakit - Maulidiah Rizki Harahap; Laela Indawati; Lily Widjaja (Publikasi Indonesia, 2022)
External cause is classifying disease with cases of injury, poisoning, and accidents, from external causes. Therefore, medical officers must be competent in coding according to ICD-10 and are required to provide precise and accurate codes. The purpose of this study was to determine the percentage accuracy of the external cause ICD-10 coding and to find out the obstacles to the inaccuracy of external cause coding. using the literature review method. The results of a literature review of 12 journals related to the coding accuracy of ICD-10 external causes in several hospitals found that the highest percentage of code accuracy was 82% with the lowest percentage of code accuracy being 0%, while the highest percentage of coding inaccuracy was 100% and for the percentage of inaccuracy. the lowest code as much as 18 %. The 10 journals above use 5M elements, namely the obstacles that are often obtained from the Man factor which consists of coders who are not careful in determining the code, the competence of medical recorders needs to be honed, and lack of effective communication between coders and officers regarding the contents. medical records. It is recommended for coders who do not understand coding to conduct seminars to learn how to do good coding, so that the percentage of inaccuracies in the hospital is reduced to a lower level.